Increasing the resilience of urban ecosystems to the challenges of modern reality - Kopiy, L. I.; Lukyanchuk, N. H.; Hnativ, I. R.; Kopiy, M. L.; Chernyavskyi, M. V.; Melnychuk, S. P. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
In conditions of high man-made pollution, green spaces around agglomerations play the role of the most important means of regulation, protection and optimization of the human living environment and the biosphere in general. The purpose of the study was to analyze the condition and vitality of Lviv trees according to certain indicators, as well as to establish their condition depending on adverse environmental factors and anthropogenic influence. The environmental conditions of the city negatively affect the vitality of woody, shrubby, and herbaceous plants. Infectious and non-infectious diseases prevail, green plantations suffer from poor care, in particular, improper pruning of the crown. It was established that the park stands of Lviv are relatively resistant to adverse environmental factors and anthropogenic influence.